Origin of Enrollments, Accredited Colleges and Universities, Fall Semester 1971 - Kentucky Council on Public Higher Education, Frankfort; Kentucky Council on Public Higher Education, Frankfort ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1972)
This document presents a delineation of student enrollments for the fall semester 1971 from the 43 accredited Kentucky colleges and universities. The enrollments are aggregated by institution, state, foreign country, and Kentucky resident students by county of origin. Some of the major findings of the study include: (1) The total enrollment of Kentucky colleges and universities increased 6.1% for fall 1971 for a new high of 97,984 students; (2) 80,583 Kentuckians enrolled in the accredited colleges and universities; (3) First-time freshmen enrolled in Kentucky colleges and universities increased to 22,687 for fall 1971, an increase of 7% over 1970; (4) 18,682 Kentuckians enrolled as first-time freshmen for the fall 1971; (5) Kentucky colleges and universities enrolled 17,401 out-of-state students for the fall semester; (6) Kentucky high schools graduated 42,964 students in 1971; and (7) The number of Kentuckians enrolled in Kentucky colleges and universities has increased from 65,181 in 1967 to 80,583 in 1971, representing a 23.6% increase in the 5-year period. (HS)
Educational level discussed: Higher Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Demography; Enrollment; Enrollment Trends; Higher Education; Research; Research Projects; School Statistics; Statewide Planning; Statistical Data; Student Mobility; Kentucky